Internationalization of Higher Education in Emerging Europe. A Diachronic Perspective - Constantin Halangescu (CES Working Papers, 2015)
The dynamics and implications of internationalization vary quite considerably among different regions and countries, depending on the history and structure of their Higher Education systems. With a target to become the most competitive and dynamic economy in the world, Europe has scaled academic mobility, partnerships between the European Research Area and the world's top universities. The aim of this paper is to present some considerations regarding the internationalization of academic space in emerging European countries; more specifically it is an analytical review of the opinions on the phenomenon of internationalization in diachronic perspective of its development, in order to distinguish the structural problems at the level of interference, of the internationalization strategies before the economic crisis in the academic phenomenon. It can be a point of view in order to prove (argued by some causal relationship) that the academic Emergent Europe manifest itself in a differentiated manner, even if the strategies are common.
Keywords: I23; I29; P36; 330; Internationalization; Emerging Europe; Higher Education; Bologna Process; mobility